Structures and Properties of New Organic Molecule-Based Metals, (D)2BrC2H4SO3 [D = BEDT-TTF and BETS] - Hiroki Akutsu; Yuta Koyama; Scott S. Turner; Yasuhiro Nakazawa (Magnetochemistry, 2021)
An organic anion, 2-bromoethanesulfonate (BrC2H4SO3−), provides one bis(ethylenedithio)tetrathiafulvalene (BEDT-TTF) and two bis(ethylenedithio)tetraselenafulvalene (BETS) salts, the compositions of which are β’’-β’’-(BEDT-TTF)2BrC2H4SO3 (1), β’’-β’’-(BETS)2BrC2H4SO3 (2), and θ-(BETS)2BrC2H4SO3 (3), respectively. Compound 1 shows a metal–insulator transition at around 70 K. Compound 2 is isomorphous to 1, and 3 is polymorphic with 2. Compounds 2 and 3 show metallic behavior at least down to 4.2 K. The pressure dependence of the electrical resistivity of 1 is also reported.